Food: Transformation in Social Networks - D. N. Karpova (Vestnik MGIMO-Universiteta)
The modem network and digitalized society is full of social changes in various accustomed spheres of our lives including transformation in food practices. The author gives an example of the easiest way how to book food virtually and get it home this day according to tastes of a customer. Moreover the article represents new forms of specific societies existed in the Internet called food-blogs. This, on the author's mind, changes the traditional mechanism of people's choice. Food-blogs are analyzed through the prism of multifunctionalism and dynamics of food and trust. When the process of food preparing and eating attains new communicative functions. Moreover the author notes some social reasons why one user choses this or that food-blog. For instance, the popularity of blogger and network users trust, mostly «blinded». Beside the point, the conception of «trust» used in the text is based on science works of contemporary sociologist P. Sztompka. Both socialized and communicative functions of food are described through theories of R. Bart and G. Simmel. It is underlined in the text that food transforms and gains new qualities notin traditional ways we used to think but in social and cultural construction in virtual space and through network communication.